Report on the fineness of copper - Booth, James Curtis
Tabulation of data on the fineness of copper (i.e. weight of copper in proportion to the total weight of the metal including impurities and alloy base metals.)
Keywords: Precious metals--Assaying; Copper; Smelting; Copper--Assaying; Metals--Refining; Copper industry and trade; Metallurgy; Copper--Refining; Booth, James Curtis, 1810-1888; Mint of the United States; United States Mint